2015
DOI: 10.1007/s10999-015-9297-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal location of piezoelectric actuators for active vibration control of thin axially functionally graded beams

Abstract: Up to now, optimal location for active control studies concern principally multilayers or homogeneous structures. In the case of functionally graded materials, very few papers exist and they only concern cross section variations. In this way, this paper deals with the optimization of piezoelectric actuators locations on axially functionally graded beams for active vibration control. For this kind of structures, the free vibration problem is more complicated as the governing equations have variable coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Nevertheless, spillover effect due to the truncation of the modal basis must be considered. One solution is to optimize the location of sensors and actuators by taking into account the first residual modes into the optimization process [24].…”
Section: Control Law and Observermentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, spillover effect due to the truncation of the modal basis must be considered. One solution is to optimize the location of sensors and actuators by taking into account the first residual modes into the optimization process [24].…”
Section: Control Law and Observermentioning
confidence: 99%
“…Regarding the active vibration control using functionally graded material, we can find in literature papers dealing with active vibration control of FGM equipped with piezoelectric patches [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 19 ] investigated the optimal configuration of piezocomposite actuators for bending and twisting vibration control of plate structures. Bruant and Proslier [ 20 ] employed piezoelectric actuators for active vibration control of thin, axial, functionally graded beams. Kuriakose and Sreehari [ 21 ] experimentally demonstrated that piezoelectric patches bonded on an airplane wing panel can actually sense the amount of vibration and suppress it using an active vibration control system.…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of flexible structures testing and control, it is useful to investigate the optimal configuration of the actuators and to evaluate their impact on the control performance. Extensive research on the optimal configuration of piezoelectric actuators for vibration control have been carried out (Biglar et al, 2014; Bruant et al, 2010; Bruant and Proslier, 2016; Crawley and De Luis, 1987; Han and Lee, 1999; Leleu et al, 2001; Liu et al, 2003; Qiu et al, 2007; Schulz et al, 2013; Wang and Wang, 2000). The actuators could also be optimized to enhance the shape control performance of smart structures (Gohari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%